Trend and Patterns of Research Proposals Submitted for Ethical Review in Nepal Health Research Council - Ghimire, Namita; Vaidya, Anju; Sah, Anil Kumar; Karakheti, Ashwin; Rana, Krishna; Malla, Pragya; Gyanwali, Pradip; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2021)
Background: The characteristics of research proposals submitted to the Nepal Health Research Council reflect the trend of health-related researches being conducted in Nepal. The objective of the study was to analyze research proposals submitted for the ethical review in Nepal Health Research Council from 2017 to 2019.Methods: A retrospective record review of research proposals received over three years from 2017 to 2019 were analyzed. A total of 2,305 research proposals was included in the study. The number of research studies per year, types of study design, priority area of research, and rejected proposal were the intended variables for the study. Results: 91.45% (503), 92.19% (748), and 755 (80.1%) of received proposals were approved from Ethical Review Board in 2017, 2018 and 2019. The number of research proposals increased every year (550 in 2017, 812 in 2018, and 943 in 2019). Among the approved proposals non-communicable disease (n=150;15.90%) in 2019} was the topmost prioritized area in all three years followed by reproductive health [93 (9.86%) in 2019] and communicable disease [67 (7.10%) in 2019] respectively. Quantitative research was more than two-third in all the years. Among the approved proposals, more than half were for an academic purpose [ 610 (64.69%)]. The reason for the rejection of the proposal was the conduction of research before ethical approval [2 (0.36%) in 2017, 2 (0.25%) in 2018, and none in 2019].Conclusions: There was a rising trend of research proposals for ethical clearance being submitted to the Nepal Health Research Council. Research related to non-communicable disease followed by reproductive health was the commonest one. Keywords: Ethical approval; ethical review board; research proposals; record review